De danske enstavelsesord med udlydende langvokal sproghistorisk belyst af »afstemningsteorien« - Panieri, Luca (Danske Studier, 2024)
In a recently published paper I presented a new hypothesis regarding the origin of the Danish stød connecting this phenomenon with devoicing of consonants in final position or in internal position before other devoiced or unvoiced consonants. I will here use this ‘devoicing theory’ to provide an explanation for some historical-linguistic problems linked to the presence of stød in modern Danish monosyllables, which only at first sight seem to contradict the devoicing theory itself. It will be shown, in fact, how the theory itself can be used to find a plausible explanation for such problems. In this context three different phenomena are shown to be relevant in setting up a reliable explanatory model for the above-mentioned problems: the first stage of the Old Norse development sēa > sjā ‘to see’, modern Danish schwa-assimilation and »stødefterslag« (stød afterbeat).